2021
DOI: 10.47717/turkjsurg.2021.5277
|View full text |Cite
|
Sign up to set email alerts
|

An indirect effect of COVID-19 pandemic: Increased pediatric perforated appendicitis rate due to delayed admission

Abstract: Objective: Appendicitis is a common surgical emergency among children. The coronavirus pandemic affected the system of hospitals more than any other field, and great amount of people were concerned about visiting the hospitals for any reason. In this study, it was aimed to evaluate the profile of appendicitis by emphasizing perforated and acute appendicitis in the pandemic period and to compare the rates with previous three years. Material and Methods: Charts of the children who underwent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…Ergün et al showed prolonged times between the onset of symptoms and hospital admission, longer hospitalization times before surgery and longer LOSs. Perforation rates increased by 18-19% on average during the pandemic in comparison to the previous three years [41]. Analogous results were also reported by another three authors [49,104,105].…”
Section: Time To Hospital Admission Duration Of Symptoms and In-hospi...supporting
confidence: 85%
See 1 more Smart Citation
“…Ergün et al showed prolonged times between the onset of symptoms and hospital admission, longer hospitalization times before surgery and longer LOSs. Perforation rates increased by 18-19% on average during the pandemic in comparison to the previous three years [41]. Analogous results were also reported by another three authors [49,104,105].…”
Section: Time To Hospital Admission Duration Of Symptoms and In-hospi...supporting
confidence: 85%
“…As the pandemic continued, all these factors improved; however, wide testing meant that most surgeons waited for SARS-CoV-2 PCR patient results before operating. The study by Ergün et al established with statistical significance that time from hospital admission to surgery or NOM was indeed greater during the pandemic but did not lead to increased perforation rates for children [41]. This has been the case for adults [9,92].…”
Section: Delays In Primary Operative Management or Increased Time To ...mentioning
confidence: 97%